Business Strategy Formulation to Increase Profit of Agung Artomoro Company - Mahfudhotul Ainiyah; Sonny Rustiadi (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2020)
Agung Artomoro is a service company operating since February 2012. The company was established because of the high number of migrants in Indonesia associated with the high demand for labor in the plantation industry. The company focuses on offering full package service in providing labor for plantation, providing goods for plantation labor, and providing transportation service. Since it was founded, the company continues to get a positive earning year to year, but the increase in revenue followed by an increase in the cost, and it causes profit stagnation. This research investigates what causes of the stagnation in company profit. The research question design method was used in this paper, which involves using a qualitative research interview in collecting data from 11 respondents, including internal and external parties. The external analysis results show that the pulp and paper industry is still growing, which supported by government regulation. The internal analysis results show that the company has resources and capabilities that have not been fully maximized. The conclusion of the internal and external analysis resulted in details of SWOT analysis tools and formulated into the Fishbone analysis to discover the root cause of the company's problem. This research aims to create a new business model by proposing a few strategies to increase business performance evaluation for internal development. The researcher selected two strategies obtained from Porter’s Generic Strategy, which used a vertical integration strategy, both integrating backward and integrating forward.  The results of the proposed strategies are mapped into Business Model Canvas and highlight how cost leadership strategy can maximize the use of resources and capabilities to make business performance more effective and efficient and create sustainability in competitive advantages.